AN OVERVIEW OF URBAN SANITATION IN ANDHRA PRADESH - Tentu, Ramesh; Rama Krishna Nattala, Shiva (IJRDO - Journal of Social Science and Humanities Research, 2017)
Sanitation, hygiene, and cleanliness are the hallmarks of a civilized society. Sanitation is critical for health and sustainable socio-economic development. Needless to emphasize, the quality of human life, inter-alia rests upon better accessibility to sanitation. The agenda set for providing clean water and better sanitation facilities apply more so for developing countries. For the marginalized communities, lack of clean water and adequate sanitation acts as an impediment for the Human Development growth in the communities across the world. The quality of human life, directly or indirectly, depends upon accessibility to better sanitation. In developing countries, the poor people have great burden of diseases due to inadequate water supply, sanitation and hygiene. The United Nations Millennium Declaration, in particular its eighth Millennium Development Goal, reflects the global importance of water sanitation and hygiene for development, poverty reduction and health. Governments are unable to provide basic needs to the citizens, because of the rapid increase in the urban population. Compared to rural households, urban households have 135% improved sanitation facilities and 30% have improved water source in developing countries. In Asia, the water supply and sanitation coverage is 81% and 48%, respectively. Focuses on sanitation. It seeks to present the latest evidence on the provision of adequate sanitation, to analyse why more progress has not been made, and to suggest strategies to improve the impact of sanitation, highlighting the role of the health sector. It also seeks to show that sanitation work to improve health, once considered the exclusive domain of engineers, now requires the involvement of social scientists, behavior change experts, health professionals, and, vitally, individual people. Throughout this paper, we define sanitation as the safe disposal of human excreta. The phrase ‘‘safe disposal’’ implies not only that people must excrete hygienically but also that their excreta must be contained or treated to avoid adversely affecting their health or that of other people.